(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduction - 2. The organisational structure of Mevlevi Islamic mysticism - 3. Mevlevi spirituality and religiosity - 4. The secular sphere and the laws of the market - 5. Conclusions. Abstract: This article aims to provide as comprehensive a reading as possible of the organisation of socio-religious aggregation of contemporary Islamic mevlevism in Turkey. Starting from some classical notions of religion and spirituality (Simmel, Weber, Troeltsch) we examine the type of organisational structure of the Mevlevi order, the modus operandi, the internal relations between the followers, the role of the master taking into consideration the criterion of compromise, inclusiveness/exclusiveness and the transmission of charisma. Furthermore, the nature of Mevlevi spirituality, its organisational and moral principles, and the ecstatic practice of the sema is analysed. Finally, we analyse the relations of the Mevlevi orders with the population, some kinds of financing mechanisms, some forms of mediatisation and the marketing of some Mevlevi products. Finally, the order’s interest and need to become part of religious tourism is analysed, encountering, however, conflicts, internal divisions and the non-legitimation needs of specific groups of believers.